GAMBARAN HISTOPATOLOGI GASTER MENCIT HIBRID F1 (C3HxAJ) YANG DIINOKULASI TUMOR ADENOCARCINOMA MAMMA SECARA INTRAVENA, INTRAPERITONIAL DAN SUBKUTAN - Griana, Tias Pramesti (El-Hayah : Jurnal Biologi, 2012)
The aim of the current study was to know if adenocarcinoma mamma tumor can be appear at the stomach of F1 hybrid mouse (C3HxAJ) that innoculated adenocarcinoma mamma's tumor via antravenous, intraperitoneal, and subcutaneus. Methods : The study was experimentaly  using  posttest  control  group  design,  to  examine  the  pylorus  mucosa thickness, the number of metaplasia, hyperplasia, and inflammatory cell. Result : There were no metaplasia and hyperplasia but inflammatory cell has been found. Analize of the pylorus mucosa thickness and the number of inflammatory cell by Oneway ANOVA showed there was no significant different of control group and manipulated group (intravenous, intraperitoneal and subcutaneus) (p0.05). Conclution : Adenocarcinoma mamma's tumor has been not found at the stomach of F1 hybrid mouse (C3HxAJ) that innoculated with via intravenous, intraperotoneal and subcutaneus.